2016
DOI: 10.1021/acs.jpcc.6b10432
|View full text |Cite
|
Sign up to set email alerts
|

High Water-Splitting Efficiency through Intentional In and Sn Codoping in Hematite Photoanodes

Abstract: The effects of intermittent thin ITO layers on the water-splitting efficiency of α-Fe2O3 films grown by PECVD on FTO substrates are reported. The α-Fe2O3 was codoped with indium and tin by temperature-driven ionic transport and diffusion from the ultrathin ITO layer sputtered between the α-Fe2O3 layer and FTO substrate. The α-Fe2O3/ITO/FTO photoanodes showed a remarkable interdependence between the thickness of the ITO layer and PEC efficiency. Hematite photoanodes with a 32 nm thick ITO underlayer showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 53 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…Several modifications have been developed to ameliorate it, including the construction of passivation layers [10] , catalyst loading [18] , and building heterojunction [19,20] . Bimetallic doping is an important and facile way to elevate the conductivity and reduce recombination simultaneously [21][22][23] . Jun Wang et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several modifications have been developed to ameliorate it, including the construction of passivation layers [10] , catalyst loading [18] , and building heterojunction [19,20] . Bimetallic doping is an important and facile way to elevate the conductivity and reduce recombination simultaneously [21][22][23] . Jun Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al . [22] fabricated In, Sn co-doped hematite by inserting an ITO layer and demonstrated that they can reduce the recombination of electrons and holes. Si, Ti [23] and Sn, Zr [24] codoped hematite had also been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…Element doping (i.e., addition of Ti, Si, Pt, Sn, P and Zr) [8][9][10][11][12][13][14][15][16][17][18] has been recognized as an efficient and widely used method to enhance the PEC activities of hematite photoanodes. For example, the dopant of Pt may have different states to play multiple roles in enhancing the PEC activity, 10 and non-metallic P doping can enhance the electron mobility, thus improving the PEC activity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, indium and tin elements were codoped into α-Fe 2 O 3 by temperature-driven ionic diffusion from the ultrathin ITO layer which was sputtered on the FTO substrate. It was found that a 32 nm thick ITO underlayer exhibited 3-fold photocurrent enhancement over pristine hematite at 1.23 V vs. RHE [34].…”
Section: Introductionmentioning
confidence: 99%